2018
DOI: 10.3390/ijerph15050834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Air Pollution on Pulmonary Function Level of Residents in Korean Industrial Complexes

Abstract: This study aims to identify environmental air pollution adversely affecting pulmonary function among a community-based general population living in Korean industrial complexes. A total of 1963 residents participated in a pulmonary function test (PFT). The sample population consisted of an exposed group (n = 1487) living within a radius of 5 km of industrial complexes and a control group (n = 476) living over a radius of 10 km from the industrial complexes in Gwangyang and Yeosu cities. PFT results were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Current evidence supports a strong link between short-term SO 2 exposure and reduced lung function in persons with asthma. 30,35 On the other hand, there is inconsistent evidence of an association between long-term SO 2 exposure and lung function, likely due to varying methodologies, with some studies reporting deficits 36,37 and others reporting no changes [38][39][40] in lung function. Many studies have reported an inverse association between SO 2 exposure and FVC or FEV1, but not with FEV1/FVC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence supports a strong link between short-term SO 2 exposure and reduced lung function in persons with asthma. 30,35 On the other hand, there is inconsistent evidence of an association between long-term SO 2 exposure and lung function, likely due to varying methodologies, with some studies reporting deficits 36,37 and others reporting no changes [38][39][40] in lung function. Many studies have reported an inverse association between SO 2 exposure and FVC or FEV1, but not with FEV1/FVC.…”
Section: Discussionmentioning
confidence: 99%
“…38,40 Our finding of an inverse association between SO 2 exposure and FEV1/FVC in children with asthma contrast with those from a prior negative study in children with mild-moderate asthma 40 but are generally consistent with those from a community-based study of children and adults (5-70 years old). 37 SO 2 has been shown to have potentially enhanced negative effects on lung function in persons with asthma who also have a TNF-α polymorphism at position -307…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution is known as a profound contributor to human mortality and as a potential danger to the environment and ecological systems [2,7,8]. Thus, intelligent monitoring of air pollutants is of the utmost importance to maintain acceptable levels of air quality for well-being [9][10][11][12]. 2 of 16 Among the numerous industrial pollutants, mercury contamination has been identified as one of the most acute air pollutants produced by conventional fossil-fueled power stations [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[2,7,8]. Thus, intelligent monitoring of the air pollutants is of utmost importance to maintain acceptable air quality for well-being [9][10][11][12].…”
mentioning
confidence: 99%
“…Previous studies, e.g. [7][8][9][10][11], report that a substantial amount of mercury outflows to the earth comes from coal-fired power plants. In , roughly 1960 tone/year mercury outflowed to the air from various sections worldwide [23].…”
mentioning
confidence: 99%